(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
the article examines the problem of teaching students of higher educational institutions by modern educational technologies, namely: authoritarian, didactocentric, student-oriented, humane-personal, cooperation technologies, free education, esoteric. It is shown that learning, with the help of educational technologies, ensures and accelerates the process of obtaining and assimilating new knowledge by students, and therefore contributes to improving the quality of education.